Improve the mechanism of selecting the next relay node in UAV assisted VANET - حسن, بسام; مثنى القبيلي (Latakia University Journal -Engineering Sciences Series, 2022)
The UAV_assisted VANET network consists of a group of ground nodes, which are cars and roadside units, and a group of flying nodes called drones that form a wireless network among themselves. The nodes of this network have special equipment that makes them able to communicate with each other. Routing protocols in these networks face major challenges represented by the dynamic change of network topology, as well as link disruption. A proper and effective routing protocol helps ensure that messages reach the desired destination and achieve the desired application goal. Most of the greedy geo-routing protocols in general, and GPSR in particular, focus on the Geographical location and prediction of the future location of the nodes in the process of selecting the next relay node, with the unsatisfactory consequences of interruption of the communication link and consequently low packet delivery rate and high time delay, there is a clear threat to its reliability and guarantee The communication link continues to function effectively. In this paper, we try to verify the possibility of knowing the future positioning of vehicles and drones and using them to improve the working mechanism of the GPSR routing protocol in the networks of mobile vehicles with the help of drones.